A Flexible Platform Containing Graphene Mesoporous Structure and Carbon Nanotube for Hydrogen Evolution. Issue 11 (12th July 2016) - Zhang, Rujing; Li, Xiao; Zhang, Li; Lin, Shuyuan; Zhu, Hongwei
Abstract : It is of great significance to design a platform with large surface area and high electrical conductivity for poorly conductive catalyst for hydrogen evolution reaction (HER), such as molybdenum sulfide (MoS x ), a promising and cost‐effective nonprecious material. Here, the design and preparation of a free‐standing and tunable graphene mesoporous structure/single‐walled carbon nanotube (GMS/SWCNT) hybrid membrane is reported. Amorphous MoS x is electrodeposited on this platform through a wet chemical process under mild temperature. For MoS x @GMS/SWCNT hybrid electrode with a low catalyst loading of 32 μg cm −2, the onset potential is near 113 mV versus reversible hydrogen electrode (RHE) and a high current density of ≈71 mA cm −2 is achieved at 250 mV versus RHE. The excellent HER performance can be attributed to the large surface area for MoS x deposition, as well as the efficient electron transport and abundant active sites on the amorphous MoS x surface. This novel catalyst is found to outperform most previously reported MoS x ‐based HER catalysts. Moreover, the flexibility of the electrode facilitates its stable catalytic performance even in extremely distorted states. Abstract : A free‐standing and tunable graphene mesoporous structure/single‐walled carbon nanotube hybrid membrane is designed and prepared. Amorphous molybdenum sulfide (MoS x ) is electrodeposited on this platform and excellent hydrogen evolution reaction performance is achieved, thanks to the large surface area for MoS x deposition, as well as the efficient electron transport and abundant active sites on the amorphous MoS x surface.